The Experimental Reconstruction in Bronze of a Merovingian Treasure Box from Sixth Century A.D. - Frank Willer (EXARC Journal)
Considerations about a lost ancient fabrication technique of bronze attachements from a merowingian treasure box pointed out that practical experiments had to be done to reconstruct the cast and coldwork. A self made oven and mould sould help to create a realistic situation of a merowingian workshop.